2022
DOI: 10.1186/s42492-022-00104-5
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative prediction of lymph node metastasis using deep learning-based features

Abstract: Lymph node involvement increases the risk of breast cancer recurrence. An accurate non-invasive assessment of nodal involvement is valuable in cancer staging, surgical risk, and cost savings. Radiomics has been proposed to pre-operatively predict sentinel lymph node (SLN) status; however, radiomic models are known to be sensitive to acquisition parameters. The purpose of this study was to develop a prediction model for preoperative prediction of SLN metastasis using deep learning-based (DLB) features and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
1
8
1
Order By: Relevance
“…Modeling methods using radiomics algorithm and machine/deep learning had a similar diagnostic performance. This result opposes previous evidence that suggests that machine/deep learning is superior to the traditional radiomics algorithm in predicting LNM in breast cancer (3,39,42) and requires further verification.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Modeling methods using radiomics algorithm and machine/deep learning had a similar diagnostic performance. This result opposes previous evidence that suggests that machine/deep learning is superior to the traditional radiomics algorithm in predicting LNM in breast cancer (3,39,42) and requires further verification.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, future prospective studies should improve the predictive performance of radiomics for the evaluation of LNM in patients with breast cancer and its clinical efficiency. Our meta-analysis also showed that studies using radiomics combined with clinical factors have higher diagnostic performance than those relying only on radiomics, which is consistent with the previous studies (3,25,26). Thus, adding clinical features to radiomic imaging improves the accuracy of diagnosing LNM in breast cancer.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations